A Novel Integration of PCM with Wind-Catcher Skin Material in Order to Increase Heat Transfer Rate - Seidabadi, Leila; Ghadamian, Hossein; Aminy, Mohammad (International Journal of Renewable Energy Development, 2019)
In this research, a comprehensive simulation study including 3-D Dynamic time-dependent has been performed for Phase Change Materials (PCMs) applicant as a thermal storage integrated with the wind-catcher-wall in order to reduce the temperature difference (As a sustainable cooling method) in the MATLAB open-source–code software. By means of 3-D Dynamic time-dependent, as a final finding, the temperature drop (Cooling purpose) was obtained 25 degrees at about 7 working hours. Passive cooling can be considered as a viable and attractive strategy for the sustainable concept, opposed to mitigation of energy consumption and Green House Gas (GHG) simultaneously. One of the traditional-old-age famous passive cooling systems that are still being applied nowadays is wind-catcher as an energy system. The wind catcher sustain natural ventilation and cooling in buildings through wind-driven airflow as well as temperature difference. Windcatchers can save the electrical energy used to provide thermal comfort during the hot climate in summer case of the year, especially during the peak hours contributed to energy carriers’ consumptions. In this study, by proposing a new design of the windcatchers, attempts have been made to improve the energy efficiency of passive cooling methods. Besides, the application of new efficient methods for the purpose of thermal energy storage (PCM) as a sub-system is a chosen method to increase energy efficiency. By applying energy storage systems in addition to increase system energy performance and reliability, the target of reducing energy consumption is achieved.© 2019. CBIORE-IJRED. All rights reservedArticle History: Received May 18th 2018; Received in revised form October 5th  2018; Accepted January 5th 2019; Available onlineHow to Cite This Article: Seidabadi, L., Ghadamian, H, and Aminy, M. (2019) A Novel Integration of PCM with Wind-Catcher Skin Material in Order to Increase Heat Transfer Rate. Int. Journal of Renewable Energy Development, 8(1), 1-6.https://doi.org/10.14710/ijred.8.1.1-6